Respuesta :
Good morning,
Answer:
u=-5
Step-by-step explanation:
the line D:y=-3x+b
A(-5,1)∈D ⇔ 1= -3(-5)+b ⇔ b= -14
then D:y=-3x-14
B(-3,u)∈D ⇔ u=-3(-3)-14 ⇔ u=-5
look at the photo below for more info.
____________
:)
![Ver imagen profarouk](https://us-static.z-dn.net/files/d22/e6d209cee46342cee7b582f43fb7a573.jpeg)
Answer:
u=-5
Step-by-step explanation:
the line D:y=-3x+b
A(-5,1)∈D ⇔ 1= -3(-5)+b ⇔ b= -14
then D:y=-3x-14
B(-3,u)∈D ⇔ u=-3(-3)-14 ⇔ u=-5
look at the photo below for more info.
____________
:)